CRIMINAL LAW ENFORCEMENT AGAINST CYBERBULLYING CASES IN INDONESIA - dewi, Sartika; Arafat , Zarisnov; Margayasa , Ketut (Jurnal Hukum dan Keadilan, 2025)
The development of information technology has opened up new spaces for people to communicate and express themselves through digital media. However, this progress has also given rise to new forms of crime, one of which is cyberbullying, an act of bullying carried out through electronic devices and the internet. The purpose of this study is to determine how law enforcement and obstacles to law enforcement in cases of cyberbullying. The research method used is normative juridical research with data collection using literature studies, data analysis used in this study using legal reasoning methods. The results of the study Cyberbullying is a form of bullying in cyberspace using digital technology. Law enforcement against cyberbullying is also regulated in Law Number 19 of 2016 concerning Electronic Transaction Information, formerly known as Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). In cases of cyberbullying, the Criminal Code can be used as a basis for criminal acts, such as in Articles 310, 311, and 315 of the Criminal Code. However, currently the most referred to legal basis for cyberbullying is Article 315. Obstacles in enforcing the law in cyberbullying cases include legislative factors, law enforcement factors, factors of facilities or means that support law enforcement, community factors and cultural factors.